Violation of the Unity Assumption Disrupts Temporal Ventriloquism Effect in Starlings - Feenders, Gesa; Klump, Georg M. (Frontiers in Psychology, 2018)
When stimuli from different sensory modalities are received, they may be combined by the brain to form a multisensory percept. One key mechanism for multisensory binding is the unity assumption under which multisensory stimuli that share certain physical properties like temporal and/or spatial correspondence are grouped together as deriving from one object. In humans, evidence for a role of the unity assumption has been found in spatial tasks and also in temporal tasks using stimuli that share physical properties (speech-related stimuli, musical and synesthetically congruent stimuli). In our study, we investigate the role of the unity assumption in an animal model in a temporal order judgment task. When subjects are asked to indicate which of two spatially separated visual stimuli appeared first in time, performance improves when the visual stimuli are paired (in time) with spatially non-informative acoustic cues, a phenomenon known as the temporal ventriloquism effect. Here, we show that European starlings perform better when one singleton acoustic cue is paired with the first visual stimulus as compared to pairing with the second visual stimulus. This shows, in combination with our previous study, that a non-informative singleton acoustic cue, when temporally paired with the first visual stimulus, triggers alerting while, when temporally pairing with the second visual stimulus, it prevents a temporal ventriloquism effect because the unity assumption is violated. Thus, the unity assumption influences sensory perception not only in humans but also in an animal model. The importance of the unity assumption in this task supports the idea that the temporal ventriloquism effect, similar to the spatial ventriloquism effect, is based on multisensory binding and integration but not on alerting effects.